Assessment of wheat genotypes as to their tolerance to frost in the reproductive stage - Wendt, W.; Rosa, O. S. (Pesquisa Agropecuaria Brasileira, 2014)
The assessment work of different genotypes as to their tolerance to frost in the reproductive stage, initiated in 1977, was continued In 1982 at the Centro Nacional de Pesquisa de Trigo (National Wheat Research Center). Fifty-nine genotypes, among cultivars and lines, were tested, being most of them introduced from Australia. A growth chamber was used for frost treatments in which temperatures equal or below to 0 °C were used during a 6-hour period. Minimum absolute temperatures of -4.5°C and -6.0°C were included in the program aiming to simulate frosts in different degrees of intensity. When assessing different genotypes, the following parameters were observed: spike fertility level, burning of leaves and spikes, and percentage of reduction in total grain weight. Genotypes like FTAM 28, Fronteira, and Kavkaz showed good tolerance even when submitted to frosts of higher intensity. In this paper, it is suggested that more than one parameter be used when quantifying the effects of frost on wheat in order to safely choose the material with characteristics of tolerance to this atmospheric phenomenon.